2001
DOI: 10.1128/iai.69.5.2972-2979.2001
|View full text |Cite
|
Sign up to set email alerts
|

Specific Antibodies to Porphyromonas gingivalis Lys-Gingipain by DNA Vaccination Inhibit Bacterial Binding to Hemoglobin and Protect Mice from Infection

Abstract: Lys-gingipain (KGP), a lysine-specific cysteine proteinase, is one of the major virulence factors of Porphyromonas gingivalis. Here we examined the involvement of the catalytic domain of KGP (KGP cd ) in hemoglobin binding by P. gingivalis, using a specific immunoglobulin G (IgG) elicited by the administration of plasmid DNA encoding KGP cd or the catalytic domain of Arg-gingipain (RGP cd ). The pSeq2A/kgp cd and pSeq2B/rgp cd plasmids were constructed by the ligation of kgp cd and rgp cd DNA fragments, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…7B). Of note, proteins involved in iron acquisition in other human pathogens are under intense investigation as potential therapeutic targets (1,15,19,(27)(28)(29)35). For example, antibodies directed against lipoproteins of two ABC transporters involved in iron uptake in Streptococcus pneumoniae recently were shown to be protective in a mouse infection model (1).…”
Section: Discussionmentioning
confidence: 99%
“…7B). Of note, proteins involved in iron acquisition in other human pathogens are under intense investigation as potential therapeutic targets (1,15,19,(27)(28)(29)35). For example, antibodies directed against lipoproteins of two ABC transporters involved in iron uptake in Streptococcus pneumoniae recently were shown to be protective in a mouse infection model (1).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the phenotypic expression of gingipains in P. gingivalis is involved in iron utilization and virulence (20,21,24,27,29). Specifically, a defect in the gingipain Kgp results in a non-black-pigmented mutant, thus suggesting that the accumulation of iron on the cell surface has been affected.…”
Section: Discussionmentioning
confidence: 99%
“…The number of bacteria in each suspension was estimated by determining the optical density at 600 nm and extrapolating from a standard curve, as described previously (20). P. gingivalis cells were added to a monolayer of HeLa cells (1 ϫ 10 5 cells/well) in a 24-well culture plate at a multiplicity of infection (MOI) of 200 and then incubated for 90 min at 37°C in the presence of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%